(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
In recent years, the importance of introducing financial technologies into the banking ecosystem can hardly be overestimated. Since financial technologies have changed the architecture of the financial services market. This article discusses the main causes and results from the introduction of financial services in the activities of foreign and national banks. As well as a number of recommendations for the development of the banking services market during the transformation of commercial banks in Uzbekistan.